Charles N. Myers. Education and national development in Mexico. Princeton, New Jersey : Princeton University Press, 1965. 147 p. - Lajous Vargas, Adrián (Estudios Demográficos y Urbanos, 1967)
CHARLES N. MYERS, Education and National Development in México. Princeton, New Jersey, Princeton University Press, 1965.